Interconversion of multiferroic domains and domain walls - E. Hassanpour; M. C. Weber; Y. Zemp; L. Kuerten; A. Bortis; Y. Tokunaga; Y. Taguchi; Y. Tokura; A. Cano; Th. Lottermoser; M. Fiebig (Nature Communications, 2021)
Domains and domain walls can have distinctively different physical properties. Here, the authors show how to transfer domains into domain walls and vice versa while maintaining their physical properties. Thereby the authors tune a multiferroic state between three and two dimensions.